2022
DOI: 10.1029/2022jc018406
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Slope Heat and Salt Transport Induced by Slope Intrusion Eddy's Horizontal Asymmetry in the Northern South China Sea

Abstract: Material transport caused by mesoscale eddies has been revealed much in the open ocean; however, it is still unclear how much eddy‐induced mass transport in the slope region of the northern South China Sea (SCS). Using the LASG/IAP Climate System Ocean Model (LICOM) from 2007 to 2017, we identified 47 anticyclonic eddies and 97 cyclonic eddies that intruded onto the continental slope, termed slope intrusion eddies. The slope intrusion eddies are more horizontally asymmetric and energetic than those without ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…According to Figure 9, the DSL changes noticeably when there is mesoscale eddy arrival at the location of the ADCP. Xiu and Chai (2020) and Qiu et al (2022) pointed out the negative and positive temperature anomalies in the mid-ocean of 200m-500m under the influence of cyclones and anticyclones, which fit the results of this paper. When the AEs move toward the ADCP location, isotherms bend downward, and the temperature increases in the 400-600 m layer.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…According to Figure 9, the DSL changes noticeably when there is mesoscale eddy arrival at the location of the ADCP. Xiu and Chai (2020) and Qiu et al (2022) pointed out the negative and positive temperature anomalies in the mid-ocean of 200m-500m under the influence of cyclones and anticyclones, which fit the results of this paper. When the AEs move toward the ADCP location, isotherms bend downward, and the temperature increases in the 400-600 m layer.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…This study adopts a vector geometry automatic detection method based on the geometric characteristics of mesoscale eddies (Nencioli et al, 2010). This method has already been applied to multiple data sources and complex flow fields (Dong et al, 2009;Aguiar et al, 2013;Lin et al, 2015;Sun et al, 2018;Yang et al, 2020;Sun et al, 2021a;Sun et al, 2021b;Qiu et al, 2022). Recently research has shown that the vector geometry method has more advantages than the Sea Surface Height Topology approach in terms of correct eddy identification rate and detection efficiency (You et al, 2022).…”
Section: Two-dimensional Eddy Detection Methodsmentioning
confidence: 99%
“…Mesoscale eddies are strongly nonlinear and have significant effects on physical quantities in the ocean and the atmospheric bottom boundary layer. Mesoscale eddies can transport material and energy through their horizontal movement (Dong et al, 2014), rotation (He et al, 2018) and asymmetric flow field structure (Qiu et al, 2022). Eddy-induced zonal mass transport is comparable in magnitude to the large-scale wind-and thermohaline-driven circulation (Zhang et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous mesoscale eddy studies include eddy shapes (Wang et al, 2015;Chen et al, 2021), eddy regulating ocean dynamics (Wang et al, 2018;Lian et al, 2021), heat and freshwater transport (Zhang et al, 2014;Treguier et al, 2017;Su et al, 2020;Qiu et al, 2021, Qiu et al, 2022, biochemical environment variation (Xian et al, 2012;Dawson et al, 2018;Xu et al, 2019;Ellwood et al, 2020) and energy cascade (McGillicuddy, 2015;Liu et al, 2017a;Li et al, 2018). Therefore, correctly understanding eddy distribution characteristics helps deepen the knowledge of other related issues in physical oceanography.…”
Section: Introductionmentioning
confidence: 99%